Tindak Tutur Direktif dalam Komunikasi Antarbudaya Masyarakat Kota Palu - Husnul Khatima; Asrianti; Arum Pujining Tyas (Universitas Muria Kudus, 2026)
Palu City is a multilingual and multiethnic urban space where everyday interactions frequently occur between speakers of Kaili, Bugis, and Javanese backgrounds. In such settings, directive speech acts are particularly prone to intercultural misunderstanding because they inherently demand a response and may threaten the interlocutor’s “face” when delivered without culturally appropriate mitigation. Despite abundant Indonesian pragmatics studies on directive speech acts, most focus on relatively homogeneous communities or classroom contexts, leaving limited evidence from naturally occurring intercultural encounters in public urban spaces. This study investigates the forms and functions of directive speech acts in intercultural communication in Palu City and explains how their use relates to Intercultural Communicative Competence (ICC). Employing a qualitative pragmatic approach, data were collected from naturally occurring spoken interactions in two intercultural arenas markets and a university campus through observation, non-participant listening, audio recording, and field notes. Thirty directive utterances were analyzed using Miles and Huberman’s interactive model. The findings identify six directive forms (requests, commands, questions, prohibitions, permissions, advice) and eleven functions (expressing expectations, pleading, ordering, instructing, inviting, questioning, preventing, prohibiting, permitting, suggesting, encouraging). The results highlight the role of ethnic particles and address terms as mitigation strategies and show that ICC particularly sociolinguistic, strategic, grammatical, and discourse competences shapes how directives are produced and repaired when misunderstandings arise. Practically, these insights can inform intercultural communication training and Indonesian language learning to reduce pragmatic failure in multicultural classrooms and public service encounters.